Avaliação do desempenho em sustentabilidade utilizado em processos de manufatura - Tagliari, Leandro Dóro (2020)
The adoption of sustainability in the manufacturing enables the industry to improve technologically in their economic, social and environmental performances. The industry is increasingly striving to reach sustainability through changes in products, material cycles, processes, resource recovery, and innovations in production practices. In this context, the objective of this research is to obtain a model for the assessment of sustainability performance in the comparison of manufacturing processes of conventional drilling and flow drilling. The methodology consists of three stages and each one is divided into steps. The first stage identifies the existing models that assess sustainability performance in order to obtain a wide range the aspects related to the environmental, social and economic dimensions. In the second stage, the structure of the structured procedure was defined, aiming to quantify the aspects related to the environmental, social and economic dimensions. Finally, in the third stage, the sustainability levels are determined in the environmental, social and economic dimensions, and the levels in the manufacturing area for the conventional drilling and flow drilling processes were determined. The data collected in the manufactures are quantitative and the compilation of these results was based on the multi criteria AHP method, which enabled the validation of the developed model, and the conventional drilling and the flow drilling processes were used to validate the model. The results presented will assist in the decision support process by the stakeholders of the industry, considering that the developed model may be used and adapted for any manufacturing process of the Brazilian industries.